Hubungan Durasi Penggunaan Gadget dengan Perkembangan Sosial Emosional Anak Prasekolah di TK Murai Sejahtera Kabupaten Sumedang - Ismatul Maula; Dewi Rahmayanti, Siti; Yuswandi, Yuswandi (JURNAL KESEHATAN KARTIKA, 2024)
Background: The prevalence of preschool children using gadgets has increased from 33.44% in 2022 to 38.92% in 2023. Excessive use of gadgets can have a negative impact on the social-emotional development of preschool children. Objective: This study aimed to determine the relationship between the duration of gadget use and the social-emotional development of preschool children of Murai Sejahtera kindergarten, Sumedang Regency. Method: The type of research is quantitative research using an analytic survey method with a cross-sectional approach. Sampling using a total sampling technique with 42 mothers whose children are enrolled in Murai Sejahtera kindergarten. The instruments in this study used a survey sheet for the duration of gadget use and SDQ (Strengths and Difficulties Questionnaire). The test used was Mann-Whitney. Result: The results showed that 23 (54.8%) children used gadgets >1 hour/day. Meanwhile, children's social-emotional development was normal (median = 13). The bivariate analysis results showed a p-value < α (0.007 < 0.05). Conclusion: There is a correlation between the duration of gadget use and the social-emotional development of preschool children at Murai Sejahtera Kindergarten, Sumedang Regency. Parents expect to conduct open communication with children about the benefits and risks of gadget use, set time limits for gadget use according to age, and become a good example for children in using gadgets.